2012
DOI: 10.1042/bj20120343
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of CD147-induced matrix metalloproteinase activity: role of CD147 N-glycosylation

Abstract: Degradation of the basement membrane by MMPs (matrix metalloproteinases) is one of the most critical steps in tumour progression. CD147 is a tumour-associated antigen that plays a key regulatory role for MMP activities. In the present study, mass spectrum analysis demonstrated that the purified native CD147 from human lung cancer tissue was N-glycosylated and contained a series of high-mannose and complex-type N-linked glycan structures. Moreover, native glycosylated CD147 existed exclusively as oligomers in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
105
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(107 citation statements)
references
References 45 publications
2
105
0
Order By: Relevance
“…It is now established that glycosylation is crucial to CD147 biological function, as it is the highly glycosylated species of CD147 that are responsible for the induction of MMPs and are more susceptible to clustering (Iacono et al, 2007;. Interestingly, CD147 glycosylation is attributable to N-acetylglucosaminyltransferase V (MGAT5)-generated, b1,6-branched polylactosamine (Huang et al, 2013;, a glycan structure known to act as a binding partner for galectins (Newlaczyl and Yu, 2011). ), by contrast, displayed drastic impairment of MMP9 immunostaining compared to wildtype.…”
Section: Discussionmentioning
confidence: 99%
“…It is now established that glycosylation is crucial to CD147 biological function, as it is the highly glycosylated species of CD147 that are responsible for the induction of MMPs and are more susceptible to clustering (Iacono et al, 2007;. Interestingly, CD147 glycosylation is attributable to N-acetylglucosaminyltransferase V (MGAT5)-generated, b1,6-branched polylactosamine (Huang et al, 2013;, a glycan structure known to act as a binding partner for galectins (Newlaczyl and Yu, 2011). ), by contrast, displayed drastic impairment of MMP9 immunostaining compared to wildtype.…”
Section: Discussionmentioning
confidence: 99%
“…The glycosylated forms of CD147 are highly expressed on the cell surface of various types of tumor cell, including oral, breast, lung, bladder, kidney, laryngeal, pancreatic, gastric, colorectal cancer, glioma lymphoma and melanoma (20)(21)(22). Additionally, the glycosylated forms of CD147 are able to stimulate tumor cells to produce MMPs, particularly MMP2 and MMP9 (7,8,23). CD147 is able to induce MMP expression via phosphoinositide 3-kinase/protein kinase B (Akt)/inhibitor *** of nuclear factor κB (NF-κB) (IκB) kinase-dependent IκB-α degradation, which is mediated by Ras-related C3 botulinum toxin substrate 1, NF-κB activation and by mitogen-activated protein kinase kinase 7/c-Jun N-terminal kinase-dependent AP-1 activation (20).…”
Section: Discussionmentioning
confidence: 99%
“…The extracellular region of CD147 contains three Asn glycosylation sites, and the N-glycosylation sites make similar contributions to both high and low glycoforms of CD147 (HG-CD147 and LG-CD147, respectively) (6). A number of studies have confirmed that modulation of CD147 is associated with the expression of matrix metallopeptidases (MMPs) in normal and tumor tissues (7)(8)(9). High glycoforms of CD147 (HG-CD147) stimulate the production of matrix metalloproteinase (6,7).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations